Peran Peer Teaching dalam Meningkatkan Interaksi Sosial dan Pemahaman Kognitif di Kelas - Shofi, Ajmal Ramzani Nasywa (Maliki Interdisciplinary Journal, 2024)
This article analyzes the role of peer teaching as an effective learning method in improving students' social interactions and cognitive understanding. With this approach, students teach each other, which not only deepens understanding of the material but also strengthens social and communication skills. The interactive and collaborative learning atmosphere resulting from peer teaching can increase student motivation and involvement, making them more active in the learning process. However, the application of this method faces challenges, such as differences in abilities between students and the need for guidance from teachers. Therefore, the application of peer teaching should be encouraged in the learning process to create a better and more enjoyable educational experience for all students. This article also offers strategies to overcome these obstacles, so that peer teaching can be implemented more effectively. Thus, this research confirms that peer teaching does not only focus on academic aspects, but also on students' social and emotional development, making it a valuable alternative in the context of holistic and sustainable education.